Menentukan Arah Strategis Digitalisasi Rekam Medis Elektronik Melalui Analisis SWOT dan Matriks IFAS-EFAS - Yulida, Rina; Handayani, E. Ria Susi; Nofitriyani, Nofitriyani (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2025)
Panti Rini Hospital has implemented Electronic Medical Records (EMR) to improve the quality of healthcare services. The initial development for outpatient services began in 2014, followed by inpatient development in 2022. However, its implementation still faces challenges, including limited data interoperability between units and unstable system performance. This study aimed to analyse internal and external factors influencing EMR development in the inpatient unit using SWOT analysis, as well as IFAS and EFAS matrices. A descriptive method was used, with data collected through interviews, observations, and document reviews. The findings showed internal strengths such as ease of data access, strong human resource support, and sufficient budget allocation. Weaknesses included limited IT personnel and the continued use of a hybrid system. External opportunities included policy support from the government and the Foundation, while threats involved the need for integration with the national health information system and server instability. Based on the analysis, Panti Rini Hospital was positioned in Quadrant I of the Grand Strategy Matrix, with an IFAS score of 2.84 and an EFAS score of 2.55. This indicates the hospital should adopt an aggressive strategy to strengthen EMR digitalisation and improve healthcare service efficiency and effectiveness.